Evaluation of Antibacterial Efficacy of Alchornea cordifolia Leaf Extracts against Multidrug-Resistant Enterobacteriaceae Isolated from Poultry Birds (Sahel Journal of Life Sciences FUDMA, 2025)
The continual monitoring of resistance in poultry isolates is of epidemiological significance. This study investigated the antibacterial potency of methanol extracts of Alchornea cordifolia against drug-resistant Enterobacteriaceae from healthy chickens in Umuahia, Abia State. The organisms were isolated and characterized by sequencing their 16S rRNA gene, and the antibiotic susceptibility profile was ascertained. The inhibitory activities of the extracts were tested using standard methods. Fifteen (15) microorganisms were isolated, but predominant among them were Proteus mirabilis (40.0%), Salmonella spp (26.7%), Klebsiella pneumoniae (20.0%), and Enterobacter aerogenes (13.3%). The nucleotide sequences of bacterial 16Sr RNA gene retrieved from the isolates were deposited in the GenBank database with accession numbers PQ555018 and PQ555019. The results revealed a moderate level of resistance to cephalosporins, as 40.0% of the isolates showed resistance to ceftriaxone and 46.7% to cefuroxime. Ofloxacin and levofloxacin exhibited significant activity as 73.3% and 80% of the isolates being susceptible. The predominant resistance pattern (ceftriaxone, tetracycline, and azithromycin) occurred in 93.3% of isolates. Proteus mirabilis exhibited the broadest resistance (as 5/6 of the strains were resistant to CRO-TET-CPR-AZN-GEN), while Salmonella spp and Klebsiella pneumoniaeÂ showed resistance to â‰¥5 antibiotics. The crude extracts of the leaves of Alchornea cordifolia exerted significant activity in a dose-dependent manner, with inhibition zones ranging between 11.0mm to 17.0mm at the 200mg/ml concentration. Proteus mirabilis was most susceptible to the leaf extract, as evident by its increased zone of inhibition. The potency of Alchornea cordifolia against the isolates (MIC between 12.5mg/mL and 50mg/mL) highlights its potential as an alternative therapy.